Study on imperative factors of continuous improvement tool-total quality management for improvement of organisational culture and performance towards world class. (1st January 2013) - Muthukumar, N.; Tamizhjyothi, K.; Nachiappan, R.M.
This study explores the imperative factors of improvement (CI) tool-total quality management (TQM) and investigates the influence of TQM on organisational culture and performance. With the intention of gaining more insight into the examination, the study analyses the impact of imperative factors of TQM on the cultural and world class performance indicators of organisation. The study makes use of two types of scales, namely, level scale and change scale, in order to measure (or capture) and analyse the perception of respondents in the questionnaire employed in this research work. From the analysis, it is observed that there is a considerable positive change in all the CPIs, which shows the imperative factors of CI tool-TQM have consequences and relationship on the cultural and performance indicators of organisation towards world class status. Therefore, the organisations which have not implemented CI tool-TQM are recommended for implementing CI tool-TQM towards change in organisational culture and achieve world class performance in manufacturing.